2004
DOI: 10.3168/jds.s0022-0302(04)73203-8
|View full text |Cite
|
Sign up to set email alerts
|

Peripartum Serum Vitamin E, Retinol, and Beta-Carotene in Dairy Cattle and Their Associations with Disease

Abstract: Peripartum decreases in serum concentrations of vitamins A and E may contribute to impaired immune function in dairy cows. The objectives of this study were to describe peripartum serum concentrations of alpha-tocopherol, beta-carotene, and retinol and their associations with disease risk. On 20 farms over 1 yr, blood samples were collected weekly from 1057 cows from 1 wk before expected calving until 1 wk postpartum. Serum concentrations of alpha-tocopherol, beta-carotene, and retinol, as well as several bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
104
2
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(125 citation statements)
references
References 22 publications
10
104
2
9
Order By: Relevance
“…It was also found that the live embryo number was lower in PRV-challenged mice than in PBS-treated mice when fed on vitamin E at 75 mg/kg diet, but the live embryo number didn't differ between PRV-challenged and PBS-treated mice when fed on vitamin E at 375 mg/kg diet. It was inferred that a higher amount of vitamin E may be required by PRV-challenged mice to maintain normal reproductive performance, which is in agreement with previous reports in swine (39) and cows (40).…”
Section: Discussionsupporting
confidence: 90%
“…It was also found that the live embryo number was lower in PRV-challenged mice than in PBS-treated mice when fed on vitamin E at 75 mg/kg diet, but the live embryo number didn't differ between PRV-challenged and PBS-treated mice when fed on vitamin E at 375 mg/kg diet. It was inferred that a higher amount of vitamin E may be required by PRV-challenged mice to maintain normal reproductive performance, which is in agreement with previous reports in swine (39) and cows (40).…”
Section: Discussionsupporting
confidence: 90%
“…Vitamin E neutralizes free radicals by formation of the prooxidant vitamin E radical, which under normal physiological states will be regenerated to vitamin E by GSH-Px and vitamin C. Interestingly, plasma concentrations of vitamin E decrease through the transition period and low antioxidant status is associated with disorders in transition cows (LeBlanc et al 2004). These low concentrations are also associated with increased incidence of fatty liver and displaced abomasums (Mudron et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…High NEFA (>0.4 mmol/l) in the last 7 to 10 days before expected calving is associated with: 2 to 4 times increased risk of LDA [17,47]; 2 times increased risk of retained placenta [16,48]; 2 times increased of culling before 60 days in milk (DIM) and 1.5 times increased risk of culling over the whole lactation [49]; and 1.1 kg/day less milk production in the first 4 months of lactation [50].…”
Section: Associations Of Nefa and Bhb With Disease Production And Rmentioning
confidence: 99%
“…Cows in greater negative energy balance, and in particular those that go on to have metritis or endometritis have more pronounced impairment of at least some immune functions [5]. Cows in a greater degree of negative energy balance prepartum, as evidenced by higher nonesterified fatty acid (NEFA) concentrations were 80% more likely to have RP, and accounting for the effect of NEFA, those with lower circulating vitamin E were at greater risk of RP [16]. This supports the notion that severe negative energy balance impairs immune function, which in turn makes RP more likely, but also underlines the fact that the development of RP is multifactorial.…”
Section: Introduction-metabolic Challenges In Peripartum Dairy Cows Amentioning
confidence: 99%